An Edition of Miles Hogarde's "A Mirroure of Myserie" - Sobecki, Sebastian (punctum books, 2021)
"This is the first edition of A Mirroure of Myserie (1557), a poem by the Catholic propagandist Miles Hogarde and probably presented to Queen Mary. Cast as a dream vision, this combative dialogue draws on William Langland's widely circulating medieval poem The Vision of Piers Plowman and offers a critical assessment of sixteenth-century morality in England. The Mirroure of Myserie has been edited from Huntington Library MS 121 and is accompanied by a short introduction. This accessible edition preserves Hogarde's original spelling but adds modern punctuation and glosses of all unfamiliar words and concepts."